Metabolic and renal changes in patients with chronic hepatitis C infection after hepatitis C virus clearance by direct‐acting antivirals. Issue 4 (20th March 2020) - Nevola, Riccardo; Rinaldi, Luca; Zeni, Letizia; Sasso, Ferdinando C; Pafundi, Pia C; Guerrera, Barbara; Marrone, Aldo; Giordano, Mauro; Adinolfi, Luigi E
Abstract: Background and Aim: The impact of hepatitis C virus (HCV) clearance by direct‐acting antiviral agents (DAAs) on HCV‐related extrahepatic manifestations is not well known. We evaluated the effect of viral clearance on metabolic and renal parameters. Methods: In this prospective study, HCV patients who achieved a sustained virologic response (SVR) by DAAs were evaluated before, at the end, and 24 weeks after treatment for glycemic (serum glucose and insulin, HOMA‐IR, HOMA‐β, and HOMA‐S) and lipid (serum cholesterol, triglycerides, low‐density lipoprotein [LDL], high‐density lipoprotein) metabolism and renal function (serum creatinine, estimated glomerular filtration rate [eGFR]). Results: A total of 343 consecutive HCV patients were evaluated. At 24 weeks of post‐follow‐up, an increase in body mass index (BMI) was observed ( P  < 0.05). Regardless of hepatic fibrosis levels and BMI, a reduction in serum glucose ( P = 0.001), HOMA‐IR ( P  < 0.001) and HOMA‐β ( P  < 0.001) and an increase in HOMA‐S ( P  < 0.001) values were observed at 24 weeks after HCV clearance as compared to pretreatment values; 32.4% of patients with impaired fasting glucose normalized serum glucose values and 44.6% of diabetics showed an improvement in glycemic control. In contrast, serum cholesterol ( P  < 0.001) and LDL cholesterol ( P  < 0.001) values were increased. Renal function was improved with about 10% reduction of serum creatinine values ( P  < 0.02) and an increase of eGFR ( P  < 0.001). A baseline eGFR of ≤60 mL/min/1.73 m 2 was a negative predictor of renal function improvement. HCV clearance was an independent factor improving glucose metabolism and renal function. Conclusions: Our study shows an occurrence of changes in metabolic and renal parameters in HCV patients with SVR, anticipating possible future clinical scenarios that the clinician must know for proper management. Abstract : In a prospective study, 343 patients with hepatitis C virus (HCV) infection who achieved sustained virologic response by direct‐acting antiviral agent (DAA) treatments were followed up for 24 weeks to evaluate the impact of viral clearance on metabolic and renal parameters. HCV clearance was independently associated with a significant reduction in serum glucose, HOMA‐IR, and HOMA‐β and an increase in HOMA‐S. Furthermore, an increase in serum cholesterol and low‐density lipoprotein cholesterol levels was observed. Renal function was improved with a significant decrease in serum creatinine levels and an increase in estimated glomerular filtration rate. Data show that HCV clearance by DAA induces significant changes in metabolic and renal parameters.